Celecoxib Modulates the Renin-Angiotensin System in the Adipose Tissue of Obese Mice - Lula, Jamille F.; Alves de Souza, Toni Ramos; Mendes, Keila Lopes; Paraíso, Alanna Fernandes; de Farias Lelis, Deborah; Oliveira Andrade, João Marcus; de Farias, Lucyana Conceição; Brandi, Igor Viana; Batista de Paula, Alfredo Maurício; Hilzenderguer, Aline; Sena Guimarães, André Luiz; Sousa Santos, Sérgio Henrique (Current Enzyme Inhibition, 2018)
Background: The renin-angiotensin system (RAS) is a critical contributing factor to obesity and related diseases. Several studies have shown the relationship of obesity with cyclooxygenase-2. Objectives: Based on these facts, we aimed to investigate the celecoxib oral administration (a selective anti-inflammatory inhibitor of cyclooxygenase-2 (ICOX-2)) effects, in mice fed a high-fat diet by assessing the renin-angiotensin system and inflammatory markers expression. Methods: FVB/N male mice were divided into 3 groups and fed with experimental diets, standard, high-fat diet and high-fat diet plus ICOX-2 at a dose of 100mg/kg/body weight. Body weight, food intake, blood parameters and RAS/inflammatory markers expression were assessed. Results: The main findings showed that diet-induced obese mice treated with COX-2 inhibitor showed significantly improved glucose and insulin homeostasis, presented decreased body weight gain and the biochemical analyses revealed reduced triglyceride levels and higher serum HDL-c levels as compared to HFD and ST. These results were accompanied by a downregulation of AGT, ACE, TNF-α and IL-6 expression in the group receiving treatment. Conclusion: Taken together, these results indicate that ICOX-2 may exhibit therapeutic potential for obesity via the renin-angiotensin system and inflammation.
Keywords: renin-angiotensin system